Network analysis of seed flow, a traditional method for conserving tartary buckwheat (Fagopyrum tataricum) Landraces in Liangshan, Southwest China - Song, Y.; Fang, Q.; Jarvis, D.; Bai, K.; Liu, D.; Feng, J.; Long, C. (MDPI, 2019)
The Yi ethnic group in Liangshan Prefecture, Sichuan Province in Southwest China have cultivated Tartary buckwheat (Fagopyrum tataricum) for at least a thousand years. Tartary buckwheat landraces are maintained through their traditional seed system. Field work and social network methodologies were used to analyze the seed sources and their flows, and to create a seed network map. Self-saving, exchanging with neighbors and relatives, and purchasing from the market were the main means farmers used to save and exchange Tartary buckwheat seeds. The flow of seed within villages was higher than between villages. Wedding dowry was an important pathway for seed flow among all of the villages. Of the 13 Tartary buckwheat landraces maintained, four landraces were exchanged frequently. The seed exchange network structure was affected by the number of Tartary buckwheat landraces, the age of nodal households, geographic environment, culture, and cultural groups. Nodal households play an important role in the conservation and on-farm management of Tartary buckwheat landraces.